Indonesian High School Students’ Perception of Scientific Experiment Using Network Analysis: Differences between Science and Humanities Group - Aini, R. Q.; Rusmana, A. N.; Lee, J. K.; Shin, S.; Ha, M.; Sya’bandari, Y. (Jurnal Pendidikan IPA Indonesia, 2019)
Understanding what students know about the scientific experiment is essential for their metacognition and their understanding of scientific inquiry. A total of 425 Indonesian high school students participated in this study. Using an open-ended question, this study examined science and humanities group studentsÃ¢â‚¬â„¢ perception of a scientific experiment by their narrative explanations. Language network analysis method was used to measure and visualize their perception by examining the relationship between each word of response and its patterns underlying the network. After the process of network analysis, nodes Ã¢â‚¬Å“proveÃ¢â‚¬Â, Ã¢â‚¬Å“observationÃ¢â‚¬Â, Ã¢â‚¬Å“problemÃ¢â‚¬Â Ã¢â‚¬Å“hypothesisÃ¢â‚¬Â only found in science students group while nodes Ã¢â‚¬Å“newÃ¢â‚¬Â Ã¢â‚¬Å“objectÃ¢â‚¬Â Ã¢â‚¬Å“tryÃ¢â‚¬Â Ã¢â‚¬Å“testÃ¢â‚¬Â found in humanities students group. This result also perceived that science students group considered a scientific experiment as an inquiry process while humanities students were more likely into the discovery process. The result of this study could support how scientific experiment as a learning activity was taken differently in science and humanities class in high school.